Avaliação da eficiência e segurança do Sugamadex na reversão do bloqueio neuromuscular profundo induzido pelo rocurônio em pacientes com insuficiência renal crônica submetidos a transplante renal - Souza, Camila Machado De [UNIFESP] (2019)
Introduction: In patients with renal failure different physiologic and pharmacologic factors impact pharmacokinetics and pharmacodynamics of nondepolarizing neuromuscular blockers making recovery of neuromuscular function unpredictable. It’s commonly necessary to antagonize neuromuscular blockade at the end of a surgical procedure, to guarantee neuromuscular function is reestablished upon emergence and avoid severe complications like hypoxemia and aspiration. Sugammadex antagonizes rocuronium-induced neuromuscular blockade by encapsulating rocuronium, creating a stable complex molecule that is mainly excreted by the kidneys. Therefore, its pharmacokinetics is profoundly altered in kidney failure. Objective: The objective of this study is to compare the efficacy and safety of sugammadex in reversing profound neuromuscular block induced by rocuronium in patients with end-stage renal disease and those with normal renal function. Method: This prospective clinical trial was performed in two different university hospitals from 1 October 2011 to 31 January 2012 and included 20 patients with renal failure [creatinine clearance (ClCr) <30 ml.min-1] and 20 control patients (ClCr >90 ml.min-1) submitted to elective procedures and kidney transplant. Neuromuscular monitoring was performed by acceleromyography and train-of-four (TOF) stimulation. Profound neuromuscular block (post-tetanic count, one to three responses) was maintained during surgery and reversed with sugammadex 4 mg.kg-1 on completion of skin closure. The efficacy of sugammadex was evaluated by the time taken for the TOF ratio to recover to 0,9. The safety of sugammadex was assessed by monitoring for recurrence of neuromuscular block every 15 min for 2 h postoperatively. Secondary variables were time to recovery of TOF ratio to 0.7 and 0.8. Results: After sugammadex administration, the mean time for recovery of the TOF ratio to 0,9 was prolonged in the renal failure group (5.6  3.6 min) compared with the control group (2.7  1.3 min, P=0.003). No adverse events or evidence of recurrence of neuromuscular block were observed. Conclusion: In patients with renal failure, sugammadex 4 mg.kg-1 effectively and safely reversed profound rocuronium induced neuromuscular block, but the recovery was slower than healthy patients.